(NsBORNIK ZADA^ PO ANALITI^ESKOJ GEOMETRII I LINEJNOJ ALGEBRE (B:s (Nu^EBNOE POSOBIE (B/s - (NbEKLEMI[EWA(B, (Nl@DMILA aNATOLXEWNAs; (NpETROWI^(B, (NaLEKSANDR `RXEWI^s; (N~UBAROW(B, (NiGORX aNDREEWI^s; (NbEKLEMI[EW(B, (Nd(B.(Nw(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 496 (17 (NNAZW(B.)s
(NbIBLIOGR(B.: (NS(B. 496s
Keywords: (NlINEJNAQ ALGEBRAs; (NgEOMETRIQs